A força inventiva da voz ignorada - Assy, Maria Rita do Amaral (2014)
This study developed a proposal for listening interviews with workers and families attracted to work in the construction site of Sobradinho/Ba dam in the late 1970 s. Interviewees, as research shows, are ignored people, which is quite different than being exploited , decimated , oppressed , and isolated . It is not easy to understand them as a social class neither as a people. Somehow, this condition of being ignored marked the occupation of the region called lower-medium São Francisco . However, it is not a condition that is exclusive to these people. The forms of domination imposed on us since colonization have left empty spaces due to strategic reasons, and they were occupied with other means of life. It was the locus of domination where dominators were absent. It was the locus where smaller forces gained time. There is intensive existential production in this ignored locus. Only getting closer to this ignored existence makes it possible to see it. Audio was recorded about twenty years after the completion of construction. In the recordings, at the same time as one hears the conveyance of communication, of information, and the situation of interview becomes clear, ignored voices modulate the sound of the still-living marks of the fact. Will the meeting of this form of language matter be capable of housing a field where voices operate and listeners can see themselves in the struggle with the world? Said in another way, is it possible that, after interpreted by editing and mediated by technological devices, voice performance forces operate as thought, activating the invention of themselves and the world? What about academia, where only information is usually extracted from interviews, that is, one listens only that which was pre-established by the researcher? To answer that, this paper proposes a quality of attention in which it is possible to listen with concentration, however without focus, like a deer hunter, who perceives the landscape and the landscape that perceives him; and weaves a text following excerpts of the interviews, giving up this form of attention. Successive listening may provide the exercise of the same type of attention to the reader-listener and, who knows, not a new version of the construction of Sobradinho dam, neither a historical reconstitution of that period, but other ways of thinking. This is the thesis